A Molecularly Defined Iron‐Catalyst for the Selective Hydrogenation of α, β‐Unsaturated Aldehydes. Issue 24 (6th May 2013) - Wienhöfer, Gerrit; Westerhaus, Felix A.; Junge, Kathrin; Ludwig, Ralf; Beller, Matthias
Abstract A selective iron‐based catalyst system for the hydrogenation of α, β‐unsaturated aldehydes to allylic alcohols is presented. Applying the defined iron–tetraphos complex [FeF(L)][BF4] (L=P(PhPPh2)3) in the presence of trifluoroacetic acid a broad range of aldehydes are reduced in high yields using low catalyst loadings (0.05–1 mol %). Excellent chemoselectivity for the reduction of aldehydes in the presence of other reducible moieties, for example, ketones, olefins, esters, etc. is achieved. Based on the in situ detected hydride species [FeH(H2)(L)]+ a catalytic cycle is proposed that is supported by computational calculations.